TUGAS DAN KEWENANGAN BADAN KOORDINASI PENANAMAN MODAL DAERAH DALAM PENANAMAN MODAL DI PROVINSI BALI - Suryaningrat, I.B. Gede Agung; Rudy, Dewa Gde; Purwanti, Ni Putu (Kertha Semaya : Journal Ilmu Hukum, 2015)
A paper entitled "Duties and Authority of the Regional Investment CoordinatingBoard In Investment In Bali Province" is motivated by the formation of the coordinatinginstitution for the Regional Investment Coordinating Board (BKPMD) which is charged withoverseeing the implementation of capital investment in the province of Bali. On the otherhand, there is the Investment Coordinating Board (BKPM) formed by the central governmentstill has the authority related to the implementation of investment in Indonesia. For thisreason this paper is made in order to determine the duties and authority BKPMD investmentin Bali as well as to know the requirements and procedures that must be followed wheninvestors want to make investments in the province of Bali. By using the method of empiricalresearch juridical, it is found that the results into conclusions in this paper are: the dutiesand authority of the Province of Bali BKPMD the capital investment associated only withsupervision in the areas of licensing, while the authority to decide whether or not to investand registration may be investment in Province Bali is still the authority of BKPM /government. Requirements and procedures that must be followed when investors want tomake investments in the province of Bali is set in the Decree of the Head of BKPM No. 57 /SK / 2004 on Guidelines and Procedures for Investment for the Purpose of DomesticInvestment and Foreign Investments (Decree of the Head of BKPM No. 57 / SK / 2004).
Keywords: Task, Authority, Regional Investment Coordinating Board, Bali Province